Beyond the Big Five: Personality and Job Performance in an E-Commerce Firm - Sjöberg, Lennart (Journal of Advances in Management Sciences & Information Systems, 2016)
The purpose of this paper was to investigate of the relationship between personality and job performance with employees of a rapidly expanding Swedish e-commerce firm. Two studies were carried out with the UPPTM test of personality. In Study 1, seventy persons took the test on an Internet site. Three groups at NN AB participated: a group of top performers, selected by management, a group of employees selected at random, and 8 members of NN AB's top management. In Study 2, the validity of the UPPTM test was investigated with relation to supervisor assessments in a group of employees in customer service at NN AB. In Study 1, large and significant differences were found between the group of employees selected at random, and the other two groups. In terms of correlations, validity was = 0.44. In Study 2, the tested subjects were assessed by supervisors using a comprehensive assessment form (40 variables), which could reduced to three criterion dimensions. The validities for the three criterion dimensions of value for the company (halo), efficiency and social functioning were 0.66, 0.52 and 0.40. Analysis of proxy criteria (work motivation and similar attitude scales) gave similar results